The Simulation of Very High Frequency (VHF) Voice Communications at Aeronautical Mobile Satellite (Route) Service (AMS(R)S) - AA Kompiyang Karmana Putra; Muhammad Suryanegara (Politeknik Piksi Ganesha Indonesia, 2023)
To expand the coverage of current aviation VHF communication services, it is necessary to develop a satellite-based VHF communication system. This research aims to analyze the satellite link budget calculations for VHF AMS(R)S frequencies using a Low Earth Orbit (LEO) satellite at an altitude of 600 km, in accordance with the studies conducted by ICAO and ITU. The link budget calculation, using parameters such as aircraft antenna gain = -1 dBi, satellite antenna gain = 8 dBi, RF power of the aircraft = 16 watts, and RF power of the satellite = 85 watts, results in satellite receiver sensitivity between -107 dBm - 25.56 dB, as well as aircraft receiver sensitivity between -93 dBm - 38.65 dB. When simulating an end-to-end link budget (loopback: aircraft-satellite-aircraft between 14.92 dB - 14 dB. Simulations were also carried out for voice communication using an AWGN channel illustration with an Eb/No of 10 dB, resulting in the performance of the VHF audio link.